(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
In order to study the effectiveness of water and energy resources in the irrigation of agricultural crops from the ground up in 2021, the Tashkent Institute of Irrigation and Agricultural Mechanization Engineers National Research University Scientific Training Center located in Ortachirchik district of Tashkent region "Use of water-saving technologies" based on the results of scientific research at the landfill. For the study, 0.12 hectares of soil was planted with amaranth in a drip irrigation area. The vegetation period of the amaranth crop lasted 5 months. During the growing season, 9 irrigations were carried out. A total of 116,334 m3 of water was used to irrigate this area. This amount is 969.45 M³ per hectare. 116,334 m3 of water used for irrigation is 1.96 MJ per unit of energy. The energy used for agro-technical activities totaled 1979,472 megajoules. The yield of amaranth from 0.12 hectares was 310 kg. This amount is 310 kg per 1 hectare area. The yield of 310 kg of amaranth per unit of energy was 4815.24 Megajoules. Based on the results of the study, the water and energy efficiency of drip irrigation of amaranth was 2821,382 Megajoules, or 241.5%.